Letter - Isaacs, George Alfred, 1883-
1943-01-26 "NATSOPA" TELEPHONES TELEGRAMS WATERLOO "NATSOPA 4764-4765 SEDIST, LONDON" THE NATIONAL SOCIETY OF OPERATIVE PRINTERS AND ASSISTANTS TRADE UNION APPROVED SOCIETY 292 "CAXTON HOUSE" 13-16 BOROUGH ROAD ST GEORGES CIRCUS LONDON S.E.1. ASSISTANT SECRETARIES W. TIDMARSH W. PLUNKETT H GOOD GENERAL SECRETARY GEORGE A. ISAACS J.P. M.P. GI/CK. PLEASE ADDRESS YOUR REPLY TO General Secretary. DATE 26th January, 1943. Mr. H.V. Tewson, Assistant Secretary, Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, We have received an appeal from the National Joint Committee for Spanish Relief and Basque Childrens Trust Ltd., for financial assistance and I am wondering whether the Trades Union Congress has any fund by which they are assisting this body? My Executive would like to make a grant but would prefer to do this through the T.U.C. rather than make the grant direct. Can you give me any help in this matter? Yours sincerely, Geo Isaacs General Secretary. 292/946/38/21(II)